The Effect of Moringa Leaf Brewing on Blood Pressure in Hypertension Sufferers - Juli Andri; Bella Juwita; Andry Sartika; Padila Padila; Muhammad Bagus Andrianto (JOSING: Journal of Nursing and Health, 2026)
This study aimed to determine the effect of Moringa leaf decoction on lowering blood pressure in hypertensive patients in the Kandang Community Health Center (Puskesmas) area, Bengkulu City. This study was quantitative, using a quasi-experimental approach with a single-group pre-test and post-test design. The statistical analysis of Moringa leaf decoction showed a p-value of 0.000 ≤ 0.005. In conclusion, there was an effect after administering Moringa leaf decoction to hypertensive patients in the Kandang Community Health Center area, Bengkulu City. Keywords: Moringa Leaves, Hypertension, Blood Pressure